PENGARUH NPM, ROA, DER DAN EPS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA INDEKS SAHAM SYARIAH INDONESIA (ISSI) PERIODE 2018 – 2021 - Sandiawati, Fina; Hidayati, Amalia Nuril (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
This research is aimed to find out how the effect of net profit margin (npm), return on assets (roa), debt to equity ratio (der), and earning per share (eps) has on stock prices in food and beverage sub-sector companies listed on the index. indonesian sharia shares (issi). this research uses a quantitative approach, with the type of associative research. using secondary data in the form of quarterly financial reports of food and beverage sub-sector companies listed on the indonesian sharia stock index. the population used is all food and beverage sub-sector companies registered at issi during the 2018-2021 period, namely 29 companies. the sampling method used is purposive sampling. the results showed that partially the npm, roa, and eps variable had a significant effect on stock prices in food and beverage subsector companies. the der variables has no significant effect on stock prices in food and beverage subsector companies. simultaneously the variables npm, roa, der, and eps together have a significant effect on stock prices